MO717EFFECT ON BLOOD PRESSURE OF UNCOMPENSATED 130 MM SODIUM DIALYSATE IN CAPD PATIENT WITH RESISTANT HYPERTENSION. (29th May 2021) - Borrelli, Silvio; Bonomini, Mario; Arduini, Arduino; Palumbo, Roberto; Vecchi, Luigi
Abstract: Background and Aims: In peritoneal dialysis (PD) blood pressure (BP) control is largely unsatisfied mainly due to sodium retention. Currently, sodium removal in PD patients depends substantially on ultrafiltration. Lowering sodium in PD solution might improve sodium removal by diffusion, though the real benefit of low PD solution remains still undetermined. Method: In this case report, we used a novel uncompensated glucose-based PD solution (DextroCore LS, Iperboreal Pharma, Italy) containing 130 mM sodium to treat resistant hypertension in 78-year-old female treated by CAPD (3 dwells glucose 1.5% a day, Na 132). Results: At baseline, Ambulatory BP monitoring (ABPM) showed 24h-BP (152/81 mmHg), diurnal BP (151/83 mmHg) and nocturnal BP (153/75 mmHg), with inversion of circadian rhythm in systolic BP (systolic night/day ratio: 1.02), despite the use of three anti-hypertensive (doxazosin 4mg, amlodipine 10 mg, telmisartan 80 mg) and diuretic (furosemide 250 mg) at adequate doses. She had no signs of hypervolemia. We switched from standard PD (132 mM/L) to low sodium PD solution using 1.5% glucose bags with sodium concentration of 130 mM. CAPD schedule was confirmed. Second ABPM after six months reported a reduction 24h BP (131/73 mmHg), diurnal (134/75 mmHg) and nocturnal BP (122/67 mmHg), with restoring of circadian BP rhythm. No change in body weight, UF and residual diuresis was found. Diet and therapy prescriptions were unmodified. No side effects were reported. Conclusion: Six-months PD treatment with uncompensated glucose-based PD solution containing 130 mM sodium in all daily dwells has allowed to reduce systolic BP (-16 mmHg) in a CAPD patient affected by resistant hypertension, with no change in ultrafiltration and residual diuresis.